One-pot synthesis of telluroketene acetals and haloketene acetals using sp(2) geminated hetero organobismetallic intermediates - Guerrero, Palimecio G.; Oliveira, Paulo R. de; Baroni, Adriano C. M.; Marques, Francisco A.; Labes, Ricardo; Dabdoub, Miguel J. [UNESP] (Elsevier B.V., 2012)
A novel one-pot synthesis of 1,1-dihalo-1-alkenes and 1,1-bis(butyltelluro)-1-alkenes was developed from hydrozirconation of alkynylzinc bromide with Cp2Zr(H)Cl and subsequent capture of the Zn/Zr 1,1-heterodimetallo-1-alkene intermediates with halogen and tellurium electrophiles. These protocols, which include multiple reactions in a one-pot procedure, allow the preparation of the potentially useful haloketene acetals and telluroketene acetals from terminal alkynes, under mild conditions and in a good yield. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Zn/Zr sp(2) organobismetallic; Telluroketene acetals; Haloketene acetals; One-pot